Automatização de operações de registros de banco de dados em equipamentos do setor de telecomunicações - Giaretta, Jean Francisco (2024)
This article presents the development of an automated script for massive insertion and deletion of records of damaged equipment in an Oracle database, applied to the telecommunications sector. The solution, developed in Python using SQLPlus, aims to optimize the management of large volumes of data, ensuring integrity, consistency, and scalability of operations. The tests conducted demonstrated a reduction of up to 99.67% in execution time compared to the manual method for volumes of up to 10,000 records. In addition to increasing operational efficiency, the script significantly reduces the likelihood of human errors and ensures high-quality data processing, providing a robust and adaptable solution to the growing demand for real-time data management in telecommunications networks.